2009
DOI: 10.1111/j.1468-3148.2008.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Empowerment: A Place for Rich and Multiple Media?

Abstract: Environments) 1 was about exploring the terms on which young people with intellectual disability access and participate with e-Learning and the Web. The current study is one of a number of related studies. It explores the culture of information and communication technology (ICT) and the potential to support communication and empowerment. Materials and Methods Semi-structured interviews were carried out with 20 young people with intellectual disability. The interviews involved a low-technology, augmentative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…From the preceding discussion it appears that the nature of computers and websites do not currently facilitate access for people with ID [69], but despite this, support can enable online access. At the most basic level, instruction in simple computer skills (e.g., how to use a mouse or navigate a webpage) can facilitate Internet usage for people with ID [32,39,90].…”
Section: Support Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…From the preceding discussion it appears that the nature of computers and websites do not currently facilitate access for people with ID [69], but despite this, support can enable online access. At the most basic level, instruction in simple computer skills (e.g., how to use a mouse or navigate a webpage) can facilitate Internet usage for people with ID [32,39,90].…”
Section: Support Strategiesmentioning
confidence: 99%
“…Bunning et al (2009) [69] found that some people with ID expressed difficulties using ICT related to operational aspects of the technology. The severity of cognitive impairment is also likely to be a key consideration.…”
Section: Individual Impairment Associated Challenges In Accessing Thementioning
confidence: 99%
See 1 more Smart Citation
“…Research on how assistive technology can support and empower people with intellectual disabilities is a growing field (Bunning, Heath, & Minnion, 2009). Several studies show, for instance, how the adoption of certain mobile technology software and support programs can provide skill development and social participation (Darcy, Maxwell, & Green, 2016).…”
Section: Participation and The Internetmentioning
confidence: 99%
“…The few studies that do specifically address intellectual disability and accessibility are mostly published in specialist journals such as International Journal of Language and Communication Disorders, Journal of Applied Research in Intellectual Disabilities, or Journal of Research in Special Educational Needs, further evidence that ID is its own specialized area, somewhat marginal from "mainstream" disability and accessibility studies. Some studies acknowledge that the Web holds much promise for people with ID (e.g., Bunning et al 2009), and others point out that even WCAG-compliant sites are inaccessible for this audience (e.g., Small et al 2005). Other studies identify accessibility issues for people with ID (Harrysson et al 2004) or accessibility solutions for ID audiences (Brown et al 2002;Karreman et al 2007).…”
Section: Intellectual Disability: the Missing Link In The Accessibilimentioning
confidence: 94%